If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + 8x = -3x + 4(-2 + 3x) -1 + 8x = -3x + (-2 * 4 + 3x * 4) -1 + 8x = -3x + (-8 + 12x) Reorder the terms: -1 + 8x = -8 + -3x + 12x Combine like terms: -3x + 12x = 9x -1 + 8x = -8 + 9x Solving -1 + 8x = -8 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -1 + 8x + -9x = -8 + 9x + -9x Combine like terms: 8x + -9x = -1x -1 + -1x = -8 + 9x + -9x Combine like terms: 9x + -9x = 0 -1 + -1x = -8 + 0 -1 + -1x = -8 Add '1' to each side of the equation. -1 + 1 + -1x = -8 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = -8 + 1 -1x = -8 + 1 Combine like terms: -8 + 1 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| .04x+.06(30)=9.8 | | 3(w+6)+2w=-22 | | -8x-8(x-3)=5(x+9)+7 | | 36=3u+6(u-3) | | -9-x=-6(2x+7) | | -5x+4x+20-10x= | | -11=7y+8(y+8) | | -22+6r=-8r-6(1-r) | | 2a+a=-21 | | (750-x)-600-y=3x-y | | 120.08=2808.97(r) | | (2y-80)=(y+9) | | 7(d-3)+6= | | (8x+12)=(10x-24) | | 3x-4+4x+8+x=180 | | (x+30)=(2x) | | 7x-4x+x-4+3x= | | 6.5x-5+x-1.2= | | 4b-6-9b-8= | | 682/d=21 | | (3x-15)=(2x+25) | | -5=5x+5y | | 50(t)=-16t^2+50o | | 50(t)=-16t^2+ho | | h(t)=-16t^2+ho | | 2(-8)-21(-8)-7= | | 25-15(-8)= | | 45=9/2h | | 25-15(8)= | | 45=1/2h(9) | | 2(8)-21(8)-7= | | ×=2/3 |